(untitled) (Agricultural Engineering, 2019)
The aim of the study was to assess the selected physical characteristics of the briquettes of English ryegrass waste biomass and its mixtures with waste components from the agri-food industry: pea husks and oat middlings. The raw materials used for the tests are characterized by high calorific value and low ash content. Among the tested raw materials, the most favorable values were recorded for oat middlings in this respect. The produced briquettes were characterized by high volumetric density and very diverse mechanical durability. At the same time, the results of the tests on the mechanical durability of briquettes indicated that the use of components of ryegrass mixtures selected for testing brought unsatisfactory results, as compared to other analyzed physical and energy features.